(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study examines trends in educated job seekers from 2015–16 to 2021–22, analyzing their educational qualifications, social categories, genders, and age groups despite their high literacy rate of over 87%. The data reveals a steady increase in job-seeking participation, highest in 2018-19 with 1188 persons and 645 persons in 2021-22. Graduate degree holders consistently represent the largest group of job seekers, while postgraduate and PhD candidates have low but gradually increasing participation. Category-wise, Scheduled Tribes (ST) show the highest growth in job-seeking participation, while General and OBC candidates remain dominant. Gender-wise, male participation leads, but female involvement has grown steadily. The 18-24 and 25-34 age groups form the majority of job seekers, reflecting the employment challenges faced by Tripura’s youth.